A Comparison of the Diagnostic Accuracy of in-situ and Digital Image-Based Assessments of Coral Health and Disease - Burns, John H. R.; Weyenberg, Grady; Mandel, Travis; Ferreira, Sofia B.; Gotshalk, Drew; Kinoshita, Chad K.; Marshall, Micah J.; Del Moral, Nicholas A. V.; Murphy, Shane J.; Pascoe, Kailey H.; Runyan, Alexandra; Spengler, Alexander J.; et al. (Frontiers in Marine Science, 2020)
The prevalence of coral disease is steadily increasing throughout the global ocean and there is a growing need for efficient methods for detecting and monitoring coral health. At present, coral health assessments are primarily conducted using in-situ surveys, which record visual observations of disease in the field. Recent technological advancements allow researchers to instead collect high-resolution imagery of benthic habitats, and these images can be used in conjunction with digital tools to assess the health of coral colonies at a later time. However, little is known about the relative efficacy or diagnostic accuracy of these two approaches. This study contrasts the diagnostic accuracy of in-situ and digital methodologies for detecting diseases affecting corals. Multiple 1-m$^2$ plots are surveyed on coral reefs located on both the windward and leeward side of Hawaii Island. For each plot, an in-situ visual analysis of coral health is conducted by a diver and images are collected and rendered into a high-resolution orthomosaic for subsequent digital analysis. Both methods assess the same coral colonies, resulting in paired health diagnoses for multiple health conditions. Lacking a gold-standard diagnosis of disease, a latent class model is used to estimate the sensitivity and specificity of both methods. We find that in-situ assessments of coral health have a higher sensitivity and lower specificity in detecting diseases when compared to digital analyses based on orthomosaics. However, the effect size is relatively modest, indicating that while the in-situ method provides a more sensitive diagnostic approach, the techniques are of comparable accuracy and should both be considered viable methods of characterizing and monitoring coral health.